Building Bowls for Miscellaneous Media - Izadi, Shahram; Harper, Richard; Taylor, Alex (Proceedings of the First International Workshop on Physicality (Physicality 2006), 2006)
This preface to the Proceedings of Physicality 2006 describes some of the work at Lancaster and in the Equator project that were the initial inspiration for this workshop. We wish to understand physicality both because it is interesting in its own right and also because the understanding can help us design novel digital and hybrid digital–physical artefacts. Our own existing work is used to propose some initial properties and issues of physicality including rules of 'natural' interaction, issues of 'itness' and continuity in time and space, the physicality and instrumentation of the human body and issues of embodiment and spatiality.